Pengembangan Sistem Informasi Kinerja Pegawai Pemerintah Kabupaten Belu - Yohanes Payong; Max Abr Lenggu; Konrardus Verini Beni; Yeremias J.I Leuhoe (CV. Multi Kreasi Media, 2024)
Conventionally recording and reporting journals or employee performance routinely every day reaps many problems. Daily employee performance reports seem slow, complicated, and the evaluation process by regional officials takes a long time. Performance monitoring is less efficient, difficulty in monitoring employee performance in real-time and less accurate due to the difficulty of a system that allows integrated data collection. SiKaP application development uses the waterfall method, with the PHP programming language and MySQL database. Employee Performance Information System (SiKaP) application as a solution for integrating data and information and reporting employee performance every day. The SiKaP application has an important role in improving efficiency, accountability and quality of service to civil servants. The SiKaP application can be used optimally to ensure that civil servants fulfill their duties and responsibilities in accordance with the established standards and main tasks and functions.